Legal Issues in Online Transactions Involving Minors - Nurfieni, Amrin; Retnaning Muji Lestari (Universitas Islam Negeri Walisongo Semarang, 2024)
The advancement of information technology has led to transactions no longer being confined to physical spaces but extending to electronic transactions. In addition to the positive impacts, this development also brings challenges, particularly concerning the participation of minors in online transactions. Problems emerge when existing regulations fail to accommodate the rapid pace of technological advancement adequately. Minors lack the legal capacity to enter into valid agreements. Based on Article 47, paragraph 1 of the Marriage Law, a person who has not yet reached the age of 18 or is not married remains under the authority of their parents. E-commerce verification technology is not yet adequately optimized to prevent minors from carrying out transactions. Irresponsible transactions carried out by minors have the potential to cause financial harm to their parents or legal guardians. Legal issues arising from online transactions involving minors include the legality of agreements, parental supervision, transaction oversight, and payment issues. Currently, no regulations in Indonesia prohibit minors from purchasing goods through e-commerce platforms. Neither the Information and Electronic Transactions Law (UU ITE), Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions nor regulations on Electronic Commerce provide concrete limitations. The challenges surrounding legal regulations governing online transactions involving minors require a comprehensive and integrated approach. Thus, there is a need for more effective legal regulations to both prevent and address the potential misuse of interests involving minors in online transactions. Kemajuan teknologi informasi menyebabkan transaksi tidak lagi terbatas pada ruang fisik, tetapi meluas hingga transaksi elektronik. Selain dampak positif, perkembangan ini juga membawa tantangan, khususnya terkait keikutsertaan anak di bawah umur dalam transaksi daring. Masalah muncul ketika regulasi yang ada tidak mampu mengakomodasi laju kemajuan teknologi yang pesat. Anak di bawah umur tidak memiliki kapasitas hukum untuk membuat perjanjian yang sah. Berdasarkan Pasal 47 ayat 1 UU Perkawinan, seseorang yang belum berusia 18 tahun atau belum menikah tetap berada di bawah kekuasaan orang tuanya. Teknologi verifikasi e-commerce belum dioptimalkan secara memadai untuk mencegah anak di bawah umur melakukan transaksi. Transaksi yang tidak bertanggung jawab yang dilakukan oleh anak di bawah umur berpotensi menimbulkan kerugian finansial bagi orang tua atau wali yang sah. Masalah hukum yang timbul dari transaksi daring yang melibatkan anak di bawah umur meliputi legalitas perjanjian, pengawasan orang tua, kekeliruan transaksi, dan masalah pembayaran. Saat ini, tidak ada regulasi di Indonesia yang melarang anak di bawah umur untuk membeli barang melalui platform e-commerce. Baik Undang-Undang Informasi dan Transaksi Elektronik (UU ITE), Peraturan Pemerintah Nomor 71 Tahun 2019 tentang Penyelenggaraan Sistem dan Transaksi Elektronik, maupun peraturan perundang-undangan tentang Perdagangan Elektronik tidak memberikan batasan yang konkret. Tantangan yang ada dalam regulasi hukum yang mengatur transaksi daring yang melibatkan anak di bawah umur memerlukan pendekatan yang komprehensif dan terpadu. Oleh karena itu, diperlukan regulasi hukum yang lebih efektif untuk mencegah dan menanggulangi potensi penyalahgunaan kepentingan yang melibatkan anak di bawah umur dalam transaksi daring.